Menemukan Kembali Resonansi - Sunardi, St. (Retorik: Jurnal Ilmu Humaniora, 2025)
Stanislaus Sunardi is a key figure in the establishment of the Graduate Program in Cultural Studies at Sanata Dharma University. He is also the initiator of this journal, Retorik: Jurnal Ilmu Humaniora. In this editorial, Sunardi conveys his reflections on USD Cultural Studies and the journal Retorik, and introduces the articles published in this special edition celebrating twenty-five years of Cultural Studies at USD.